2019
DOI: 10.15406/frcij.2019.07.00288
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides-induced carcinogenic & neurotoxic effect on human

Abstract: Human exposure to pesticides is a worldwide major health problem. In modern age, the use of pesticides on crops has developed most dangerous diseases and some of them are very harmful. Major use of pesticides on crops and direct exposure to them gives rise to neurotoxicity and also causes carcinogenic effect on human beings. A large number of research proved that pesticides have very harmful effects in both conditions whether chronic or direct exposure. In this review, we discussed about the harmful neurotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The western part of the study area is a hub for rice production 93 . The contamination of rice grains due to contaminated soils has been documented in previous investigations 94 , 95 , and the use of pesticides also increases the carcinogenic risk sometimes 91 . The local community faces a significant danger to their health if they consume any of this infected rice 96 as it has already been recorded in different rice species in previous studies from this region 47 , 49 , 50 .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The western part of the study area is a hub for rice production 93 . The contamination of rice grains due to contaminated soils has been documented in previous investigations 94 , 95 , and the use of pesticides also increases the carcinogenic risk sometimes 91 . The local community faces a significant danger to their health if they consume any of this infected rice 96 as it has already been recorded in different rice species in previous studies from this region 47 , 49 , 50 .…”
Section: Resultsmentioning
confidence: 84%
“…The higher concentration of heavy metals in soils is transferred to edible plants and pesticides that humans ingest and ultimately possess carcinogenic effects 90 , 91 . Industrial development in the study area also poses carcinogenic effects due to the addition of heavy metals in soil from the effluents 92 .…”
Section: Resultsmentioning
confidence: 99%
“…Pesticides are currently posing a threat to human health and the environment, which has aroused concerns. Data from the last two decades revealed that certain pesticides induce neurological disorders and degenerative diseases, some affect prenatal growth and create congenital malformations, and others are carcinogenic to humans [52,[58][59][60].…”
Section: Environmental Impacts Of Pesticides In Agriculturementioning
confidence: 99%
“…Even though pesticides have improved the standard of human life by controlling pests and vectors, their long-term and indiscriminate use have resulted in serious health effects. As pesticide use has increased over the past few decades, the likelihood of exposure to these chemicals has also increased considerably [ 3 ]. Increased use of pesticides is not the only problem; rather, there has been overdosage as well as mixing of different types of pesticides with the assumption of increasing their efficacy in pest control and improving productivity [ 4 ].…”
Section: Introductionmentioning
confidence: 99%